Heartbeat of Care: Exploring Radiographers’ Insights Into CPR Knowledge and Attitudes in Jordan - Aljarrah T; Alewaidat H; Oglat A; Eltahir MA; Almakhadmeh A; Alawaqla MQ; Da'meh A; Shabaitah M; Gareeballah A (Advances in Medical Education and Practice)
Tariq Aljarrah,1,2 Haytham Alewaidat,1 Ammar Oglat,3 Mohamed Abdalla Eltahir,2 Ali Almakhadmeh,1 Moath Qasim Alawaqla,2 Anas Da’meh,2 Mohammad Shabaitah,2 Awadia Gareeballah4 1Department of Allied Medical Sciences, Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Medical Radiologic Technologies, Faculty of Allied Medical Sciences, Zarqa University, Zarqa, Jordan; 3Department of Medical Imaging, Faculty of Applied Medical Sciences, The Hashemite University, Zarqa, 13133, Jordan; 4Department of Diagnostic Radiology, College of Applied Medical Sciences, Taibah University, Al-Madinah Al-Munawwarah, Saudi ArabiaCorrespondence: Tariq Aljarrah, Department of Allied Medical Sciences, Faculty of Applied Medical Sciences, Jordan University of Science and Technology, PO Box 3030, Irbid, 22110, Jordan, Tel +962 27201000-26939, Fax +962 27201087, Email tfaljarrah22@ams.just.edu.joObjective: This study aimed to assess the knowledge and attitude of Jordanian radiographers toward Cardiopulmonary Resuscitation (CPR), in addition to exploring factors associated with their knowledge and attitude.Methods: This was a cross-sectional study. Convenience sampling was used to collect data from 359 radiographers currently working at governmental, university, military, and private hospitals across the country. Data were collected using an online Google form questionnaire between October 5, 2023 and December 27, 2023. The questionnaire included questions about demographic information, knowledge of CPR, and attitude toward performing CPR. The data were analyzed using SPSS IBM software v. 28, and P-values < 0.05 were considered statistically significant.Results: A total of 359 radiographers with a mean age of 31.71± 8.22 years participated in the study. More than half of the sample were male (198, 55.2%) compared to 161 (44.8%) females. The mean scores for knowledge of CPR and attitude toward CPR were 5.74 ± 2.31 out of 10 and 3.94 ± 0.46 out of 5, respectively. Radiographers who received CPR training demonstrated significantly higher mean knowledge scores compared to those who did not receive CPR training (M=6.51± 2.14, vs M=4.73± 2.14, P< 0.001). A correlation was observed between the age and knowledge of CPR (r=0.157, P=0.003), work experience and knowledge of CPR (r=0.177, P< 0.001), and knowledge and attitude toward CPR (r=0.326, P< 0.001), whereas no statistically significant differences were observed between male and female radiographers’ knowledge (P≥ 0.05) and attitude (P≥ 0.05) toward CPR.Conclusion: Radiographers had poor knowledge of CPR. However, there was a positive attitude toward CPR. Previous CPR training and educational level were significantly associated with higher knowledge and positive attitudes toward CPR, whereas radiographers’ age and work experience were significantly associated with higher knowledge. Therefore, continuous CPR training is recommended to increase radiographers’ knowledge of CPR.Keywords: radiographers, cardiopulmonary resuscitation, cardiac arrest, knowledge, attitude